Magnetochronology of Late Miocene Mammal Fauna in Xining Basin, NE Tibetan Plateau, China. (27th December 2018) - HAN, Jian'en; SHAO, Zhaogang; CHEN, Qiguang; XU, Biao; ZHANG, Qianqian; YU, Jia; MENG, Qingwei; ZHANG, Xuefeng; WANG, Jin; ZHU, Dagang
Abstract : Abstract : The Xining basin is located in the northeastern margin of the Qinghai‐Tibet Plateau. It is a rift basin formed in Mesozoic and Cenozoic and structurally belongs to the intersection of Kunlun and Qilian Mountains. Cenozoic fluvial and lacustrine sedimentary strata are continuous in the Xining basin, with a thickness of more than 800 m, completely recording the deformation uplifting, weathering and denudation history and climate change process of the northeastern plateau. Currently, early Miocene Xijia fauna, early Middle Miocene Danshuilu fauna and late Middle Miocene Diaogou fauna are discovered in the Xining basin, which provide an important basis for the stratigraphic correlation of the Cenozoic strata in the Xining basin. However, in the next few decades, there are no reports about the large mammal fossils in the Xining basin, especially about late Miocene fauna. The author discovered a large amount of mammal fossils in the Neogene sedimentary strata in Huzhu area, Xining basin. According to the identification results of the Institute of Vertebrate Paleontology and Paleoanthropology, Chinese Academy of Sciences, these fossils mainly included Hipparion dongxiangense, Chilotherium sp., Parelasmotherium sp., Stephanocemas sp. and Kubanochoerus sp. and their age was early Late Miocene. Since the discovery of this set of fossils directly filled the blank that there were no large mammal fossils in the Xining basin in Late Miocene, it was very important for studying the magnetic stratigraphic chronology of fossil‐forming strata and establishing the paleomagnetic chronology scale plate of mammal fossils. In this paper, the paleomagnetic data of the fossil‐forming stratigraphic profile, Banyan profile, were measured and the paleomagnetic records were collected through high density sampling, and finally the paleomagnetic polarity column of the profile was established. The results showed that five positive and five negative polarity segments were recorded in Banyan profile, which corresponded well to the polarity between C3Br.1n‐C4n.2n in the standard polarity column. The age of profile top was about 7.25 Ma and profile bottom was about 8.4 Ma, with an age range of 1.15 Ma. The mammal fossils discovered this time were exposed between positive and negative polarities N5 and R5 at the bottom of the profile, corresponding to C4r.1r at negative polarity and C4n.2n at positive polarity in the standard polarity column. The age of mammal fossils was about 8.3 Ma. The paleomagnetic chronology of the strata and paleontological fossils determined the absolute age of late Miocene mammal fossils and expanded the upper age of late Miocene Xianshuihe Formation (N1 xn ) in the Xining basin, which had provided new basic data for further studying the stratigraphic deposition and correlation of late Cenozoic strata and regional environmental evolution.